Evaluasi Sistem Pendidikan Islam Di Pondok Pesantren - Firman; Kasmah; Astuti (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2026)
This study aims to evaluate the Islamic education system at Baytul Mukarramah Islamic Boarding School in Bone Regency. This institution integrates the functions of tafaqquh fi al-din, moral development, and the enhancement of students’ skills. The evaluation was conducted based on four main components: input, process, output, and outcome. A qualitative approach was employed through document analysis, observation, and a review of relevant literature related to the pesantren education system at Baytul Mukarramah. The findings reveal that the Islamic education system has been moderately effective in shaping students’ Islamic character and religious understanding. Nevertheless, several aspects still require improvement, particularly integrative curriculum management, the enhancement of teachers’ professional competence, and the strengthening of modern educational facilities and infrastructure. This study recommends the development of an adaptive educational model that is responsive to global challenges while maintaining the pesantren’s identity as a traditional Islamic educational institution.